Exploring Narratives on Negative Emissions Technologies in the Post-Paris Era - Otto, Danny; Thoni, Terese; Wittstock, Felix; Beck, Silke (Frontiers in Climate, 2021)
The 2015 Paris Agreement specified that the goal of international climate policy is to strengthen the global response to climate change by restricting the average global warming this century to ‘well below’ 2°C above pre-industrial levels and to pursue efforts to limit it to 1.5°C. In this context, ‘Negative Emissions Technologies’ (NETs) – technologies that remove additional greenhouse gases (GHGs) from the atmosphere – are receiving greater political attention. They are introduced as a backstop method for achieving temperature targets. A focal point in the discussions on NETs are the emission and mitigation pathways assessed by the Intergovernmental Panel on Climate Change (IPCC). Drawing on perspectives from Science & Technology Studies (STS) and discourse analysis, the paper explores the emergence of narratives about NETs and reconstructs how the treatment of NETs within IPCC assessments became politicized terrain of configuration for essentially conflicting interests concerning long-term developments in the post-Paris regime. NETs are – critics claim – not the silver bullet solution to finally fix the climate, they are a Trojan horse; serving to delay decarbonization efforts by offering apparent climate solutions that allow GHGs emissions to continue and foster misplaced hope in future GHG removal technologies. In order to explore the emerging controversies, we conduct a literature review to identify NETs narratives in the scientific literature. Based on this, we reevaluate expert interviews to reconstruct narratives emerging from German environmental non-governmental organizations (eNGOs). We find a spectrum of narratives on NETs in the literature review and the eNGO interviews. The most prominent stories within this spectrum frame NETs either as a moral hazard or as a matter of necessity to achieve temperature targets.